2009
DOI: 10.1097/qad.0b013e3283320ef3
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and molecular epidemiology of subtype C HIV-1 in Zimbabwe

Abstract: Objective To investigate the origins and evolutionary history of subtype C HIV-1 in Zimbabwe in a context of regional conflict and migration. Design HIV-1C pol sequence datasets were generated from four sequential cohorts of antenatal women in Harare, Zimbabwe sampled over 15 years (1991–2006). Methods One hundred and seventy-seven HIV-1C pol sequences were obtained from four successive cohorts in Zimbabwe. Maximum-likelihood methods were used to explore phylogenetic relationships between Zimbabwean HIV-1C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
(32 reference statements)
8
45
0
Order By: Relevance
“…13,6674 These analyses can contribute to the design of intervention strategies through better understanding of epidemic growth potential, or factors contributing to historical geographic spread of subtypes or recombinants. Phylogeographic approaches showed that HIV-1C in Zimbabwe expanded through multiple introductions originating in southern Africa and localized exponential growth in the 1980s corresponding to demographic and political change.…”
Section: Phylogenetics and Transmission Dynamics In Generalized Epidementioning
confidence: 99%
“…13,6674 These analyses can contribute to the design of intervention strategies through better understanding of epidemic growth potential, or factors contributing to historical geographic spread of subtypes or recombinants. Phylogeographic approaches showed that HIV-1C in Zimbabwe expanded through multiple introductions originating in southern Africa and localized exponential growth in the 1980s corresponding to demographic and political change.…”
Section: Phylogenetics and Transmission Dynamics In Generalized Epidementioning
confidence: 99%
“…We note that further subtype validation should be conducted with alternative HIV genes, such as env. 37 Ongoing surveillance and a deeper understanding of HIV variation, including factors and molecular mechanisms that affect transmission, replication, and resistance, are crucial for the development of appropriately targeted subtype-specific prevention and treatment options for populations most at risk. 5,9,21,29 Further evidence of subtype differences could drastically change the way we respond to the HIV epidemic.…”
Section: Epidemiology Of Non-b Clade Infectionmentioning
confidence: 99%
“…However, a combination of other factors may be as likely to contribute to the swift growth of HIV-1 subtype C. A founder effect, which has been hypothesized to explain the dominance of specific subtypes throughout Africa, could be relevant 31, 32 . Additionally, Tatem et al recently provided evidence to suggest that regions with greater accessibility allowing for increased mobility, such as in southern Africa, are associated with clusters of similar subtypes throughout the transportation infrastructure 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation is that subtype C has shown lower viral fitness, and therefore may result in slower disease progression compared to other subtypes 11, 3436 ; individuals with a slower progressing disease not only add person-years to prevalence estimates, but also have more opportunity to transmit their infection over a longer period of time. Finally, subtype C may be more prevalent in sexual networks with behavioral and demographic characteristics leading to higher risk for HIV-1 transmission 31, 37, 38 .…”
Section: Discussionmentioning
confidence: 99%